Analisis Faktor yang Mempengaruhi Keberhasilan Sistem Informasi Pendaftaran Online di Rumah Sakit Nasional Diponegoro Kota Semarang - Ni Made Deviana Widiantari; Sutopo Patria Jati; Rani Tiyas Budiyanti (Jurnal Manajemen Kesehatan Indonesia, 2021)
The development of online-based information technology in the health sector can improve the quality of hospital services. Currently, Diponegoro National Hospital has implemented outpatient registration based on the "RSND-Ku" android application, and 70% of patients use the application. This study aims to describe the effectiveness and factors that influence the implementation of online registration services for outpatients at the Diponegoro National Hospital Semarang by applying a quantitative method with a descriptive analytic approach to 100 patients who use online registration services aged 20-40 years. The results showed that there is a relationship between the factors that influence the implementation of outpatient online registration services, namely the p-value of system quality of 0.000, the correlation coefficient of 0.460, the p-value of the information quality value of 0.000 and the correlation of 0.472, the p-value of service quality of 0.000 and the correlation of 0.498, and use with a p value of 0.000 and a correlation of 0.441. As for further research, the researcher suggests improvements to optimize the smoothness of the system, completeness of information, updating services, and socializing the flow of online registration services.